(untitled) (Journal of The Colloquium for Information Systems Security Education, 2022)
Given the demand for Cybersecurity workforce, the goal of the RUSecure project at Radford University is to increase the pipeline of students who plan to pursue Computer Science/IT as a major with Cybersecurity as their focus. We identified a variety of challenges to the introduction of Cybersecurity topics in high school including lack of qualified teachers, limited number of students motivated to study IT topics, large number of prerequisite topics and scarcity of computing resources required for such topics. Even an introductory Cybersecurity course requires students to have a wide array of foundational knowledge in topics such as networks. Hence, Cybersecurity programs in schools/colleges are multi-semester efforts where the first couple of semesters focus on the foundations – thus only drawing motivated students as it takes multiple semesters before students work on security problems. In response to these challenges, we developed a strategy that is exciting, rigorous and easy to adapt for high school students. This strategy employs active learning in the form of capture-the-flag (CTF) contests to drive learning. Teams of three to five students work on security challenges while competing with teams from around the state, region, and Nation. Foundational knowledge is introduced on a just-in-time basis. This paper describes these contests and their effectiveness.